Multiple Phytoestrogens Inhibit Cell Growth and Confer Cytoprotection By Inducing Manganese Superoxide Dismutase Expression. (21st March 2013) - Robb, Ellen L.; Stuart, Jeffrey A.
<x xml:space="preserve">Abstract</x> Phytoestrogens are of interest because of their reported beneficial effects on many human maladies including cancer, neurodegeneration, cardiovascular disease and diabetes. As data on phytoestrogens continues to accumulate, it is clear that there is significant overlap in the cellular effects elicited by these various compounds. Here, we show that one mechanism by which a number of phytoestrogens achieve their growth inhibitory and cytoprotective effects is via induction of the mitochondrial manganese superoxide dismutase (MnSOD). Eight phytoestrogens, including resveratrol, coumestrol, kaempferol, genistein, daidzein, apigenin, isoliquirtigenin and glycitin, were tested for their ability to induce MnSOD expression in mouse C2C12 and primary myoblasts. Five of these, resveratrol, coumestrol, kaempferol, genistein and daidzein, significantly increased MnSOD expression, slowed proliferative growth and enhanced stress resistance (hydrogen peroxide LD50). When siRNA was used to prevent the MnSOD induction by genistein, coumestrol or daidzein, none of these compounds exerted any effect on proliferative growth, and only the effect of coumestrol on stress resistance persisted. The estrogen antagonist ICI182780 prevented the increased MnSOD expression and also the changes in cell growth and stress resistance, indicating that these effects are mediated by estrogen receptors (ER). The absence of effects of resveratrol or coumestrol, but not genistein, in ERβ‐null cells further indicated that this ER in particular is important in mediating these effects. Thus, an ER‐mediated induction of MnSOD expression appears to underlie the growth inhibitory and cytoprotective activities of multiple phytoestrogens. Copyright © 2013 John Wiley & Sons, Ltd.